1989
DOI: 10.1080/09553008914551501
|View full text |Cite
|
Sign up to set email alerts
|

Repair Kinetics in Mouse Lung: A Fast Component at 1·1 Gy Per Fraction

Abstract: Four experiments to measure the half-time of repair of radiation damage in mouse lung are described. Three of these experiments used two or four doses per fraction of 3.6-9 Gy. Half-times of approximately 0.6 h were found. The fourth experiment investigated repair between the two doses in pairs of small doses given daily (26F x 1.1 Gy in 13 days). Evidence was obtained of more rapid repair between these small fractions, with a half-time of 0.30 h. Using the best methods of analysis appropriate to each experime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

1992
1992
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…It is interesting that a number of reports of two-compo nent repair in other tissues are appearing in the literature, including very recently [12,17,[20][21][22]29,34,38]. Further, Denham et al [7] have suggested that a continuum of repair rates may be present, for which two components is only a poor approximation, even though attempts to deconvolute more than two components are fruitless because of the wide confidence intervals of published data from all biological experiments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is interesting that a number of reports of two-compo nent repair in other tissues are appearing in the literature, including very recently [12,17,[20][21][22]29,34,38]. Further, Denham et al [7] have suggested that a continuum of repair rates may be present, for which two components is only a poor approximation, even though attempts to deconvolute more than two components are fruitless because of the wide confidence intervals of published data from all biological experiments.…”
Section: Discussionmentioning
confidence: 99%
“…Several other tissues have also given results interpreted as bi-exponential repair, including human telangiectasia [3], human oropharyngeal mucosa [7], mouse lung [12,20,38], pig skin [22,34], rat kidney cells [21] and mouse lip mucosa [29], The experiments are technically demanding and diffi cult to analyse because too many variables become neces sary [28]. Further, Denham et al [7] have suggested that even two components are only a rough approximation to a range of multiple T l/2 values in reality.…”
Section: Introductionmentioning
confidence: 99%
“…Though there have been several experiments providing repair rates for normal lung tissue, many of which indicate the presence of both a short and long component of repair, similar analyses for lung tumors do not exist. [16][17][18][19][20][21] One study of normal lung tissue in mice showed that the slower component of repair may approach T 1=2 ¼ 4.0 h. 22 As previously stated, although no evidence indicating similar results in lung tumors exists, if T 1=2 does approach 4.0 h for lung tumors, the effectiveness of this present study would greatly diminish. Nevertheless, Fowler and Chappell did indicate a rapid repopulation of NSCLC during radiation therapy which may imply a fast component of sublethal damage repair.…”
Section: Iic Benchmarking the Lpl Modelmentioning
confidence: 57%
“…The present result should not be generalised too widely to other normal tissues. It is known that some other tissues might have two components of repair [16,17,25,26,39,41], including human tissues [10,38]* In view of this possibility, and also in view of some early clinical results which showed telangiectasia at earlier times or unexpected necrosis with PDR treatments [30], the previous radiobiological warning to keep within the cautious envelope of small doses per pulse should not be forgotten [7,14]. experiments in this laboratory [22].…”
Section: Discussionmentioning
confidence: 99%
“…Other tissues too have been reported to have a short and a long component of repair, including human telangiectasia [38], human oropharyngeal mucosa and skin [10], mouse lung [16,41], pig skin [26,39], rat kidney cells [24] and mouse lip mucosa [35].…”
Section: Discussionmentioning
confidence: 99%